CODE MIXING AND CODE SWITCHING IN UMAR KAYAM’S NOVEL PARA PRIYAYI - Waode Hamsia (Universitas Muhammadiyah Surabaya, 2015)
This study is a sociolinguistic study. Hudson (1980:4) says that sociolinguistics is the study of language in relation to society. This is to say that sociolinguistics involves the relationship between society and language. In which is an instrument for human to interact with others.Based on the definition above language and society have close relationship. The language phenomena often occur in society; they are code mixing and code switching that commonly occure in bilingual or multilingual societyThis study is limited to make description of sociolinguistic feature of Indonesian-Javanese code mixing and code switching in Umar Kayam’s Novel Para Priyayi.A descriptive qualitative method is used in this study since the data are being analyzed that are the problem of how to describe the phenomena that happen in Novel Para Priyayi. To collect the data the writer selected sentences in the novel which contain the mixing code and the switching code of Indonesian-Javanese and then organized the data on the paper by classifying them into two forms. They are the forms in the word and the phrase.There are some purposes of using code mixing and code switching in Umar Kayam’s Novel Para Priyayi which is: 1) Showing respect to priyayi, 2) Addressing a non-priyayi and 3) There is no Indonesian equivalent. Therefore using another language is more effective that depends on the situation and condition.The study is expected to be useful for readers and people who are interested in studying the sociolinguistics. This study is hoped to give an illustration of the language that is used in Umar Kayam’s Novel Para Priyayi. In the future, another study concerning about code mixing and code switching or another aspect never stops to develop. There will be a lot of sociolinguistic phenomena that can be observed in the future.